Phytophthora sojae Effector PsCRN70 Suppresses Plant Defenses in Nicotiana benthamiana - Rajput, Nasir Ahmed (Public Library of Science, 2014)

(untitled)
Phytophthora sojae, an oomycete pathogen, produces a large number of effector proteins that enter into host cells. The Crinklers (Crinkling and Necrosis, CRN) are cytoplasmic effectors that are conserved in oomycete pathogens and their encoding genes are highly expressed at the infective stages in P. sojae. However, their roles in pathogenesis are largely unknown. Here, we functionally characterized an effector PsCRN70 by transiently and stably overexpressing it in Nicotiana benthamiana. We demonstrated that PsCRN70 was localized to the plant cell nucleus and suppressed cell death elicited by all the tested cell death-inducing proteins, including BAX, PsAvh241, PsCRN63, PsojNIP and R3a/Avr3a. Overexpression of the PsCRN70 gene in N. benthamiana enhanced susceptibility to P. parasitica. The H(2)O(2) accumulation in the PsCRN70-transgenic plants was reduced compared to the GFP-lines. The transcriptional levels of the defense-associated genes, including PR1b, PR2b, ERF1 and LOX, were also down-regulated in the PsCRN70-transgenic lines. Our results suggest that PsCRN70 may function as a universal suppressor of the cell death induced by many elicitors, the host H(2)O(2) accumulation and the expression of defense-associated genes, and therefore promotes pathogen infection.